Multinational Business Finance / Ninth Edition - Eiteman David K; Moffett Michael H; Stonehill Arthur I (2001)
This book features a streamlined presentation, expanded attention to emerging markets, and a stronger managerial focus throughout. The International Financial Environment, International Financial Management and the Multinational Firm, The International Monetary System, Foreign Exchange Rate Determination, The Foreign Exchange Market, Foreign Currency Options, Measuring and Managing Foreign Exchange Exposure, Transaction Exposure, Operating Exposure, Accounting Exposure, Interest Rate Exposure and Swaps, Financing the Global Firm, Global Cost of Capital and Financial Structure, Sourcing Equity Globally, Sourcing Debt Globally, Financial Structure, Foreign Investment Decisions, Corporate Strategy: Foreign Direct Investment and Political Risk, Multinational Capital Budgeting, International Acquisitions and Valuation, Adjusting for Risk Investments, Managing Multinational Operations, Repositioning Funds, Import and Export Financing, Advanced Topics in Multinational Finance, Current Industry Financial Management Practices, Advanced Topics in Currency and Interest Rate Risk Management, Bibliography, Index.